Characterization of Bedrock Topography, Overburden Thickness and Groundwater Geochemistry in Eastern Ontario - Foubister, Shane (Université d'Ottawa / University of Ottawa, 2023)
Across eastern Ontario areas of poor water quality have been identified through several groundwater studies completed as part of the Ontario Geological Surveys Ambient Groundwater Geochemistry Program in partnership with local municipalities and conservation authorities. This study focuses on a subset of data collected between 2012 and 2017 between east Ottawa and Champlain Township along the south shore of the Ottawa River. A high degree of variability is observed in groundwater chemistry and geochemical processes which closely relate to major geologic features across the study area (~1600 km²). Over 9000 borehole records were evaluated and used to produce updated bedrock topographic and drift thickness models to better constrain geologic features in the region. These models in conjunction with geochemical results from 369 domestic well water samples highlight the significant implications that stagnant groundwater flow and preferential recharge areas have on groundwater quality across the study area.
Keywords: Groundwater; Eastern Ontario